Resistance of two sugarcane genotypes towards Sporisorium scitamineum Scoring Using Novel Method on Sugarcane buds tissue and Phenol Plant dynamics - Supriyono, Supriyono; Abadi, Abdul Latief; Syib’li, Muhammad Akhid; Hidayah, Nurul (Research Journal of Life Science, 2023)
Smut disease caused by a basidiomycete fungus, Sporisorium scitamineum, is one of major diseases on sugarcane worldwide. The disease could cause considerable yield losses up to 60% on susceptible varieties. Understanding of resistance characteristics of sugarcane clones is essential to support development of resistant sugarcane varieties to smut fungus infection. This study aimed to determine characteristics of sugarcane genotypes J19R17-325/15/3-9 and ASA Agribun toward S. scitamineum infection and the role of phenolic compound on defense mechanism of sugarcane to smut infection. The research consisted of four treatments and was arranged according to the randomized block design with five replicates. The results revealed that J19R17-325/15/3-9 produced higher phenolic compound (0,192 mg/gr) rather than ASA Agribun (0,182 mg/gr). In addition, the distribution of fungal mycelia within sugarcane tissues on J19R17-325/15/3-9 was also lower than those on ASA Agribun. These results indicated that J19R17-325/15/3-9 might have resistance properties to S. scitamineum infection.